2011
DOI: 10.1007/s13224-011-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine bleeding in peri-menopausal age: Diagnostic options and accuracy

Abstract: :Objectives: Various diagnostic techniques have been evolved over the periods to determine the etiology of abnormal uterine bleeding in peri-menopausal women, but their accuracy has not been compared properly. In this study diagnostic accuracy of trans-vaginal sonography (TVS), saline infusion sonography (SIS) and dilatation & curettage (D & C) were compared with hysteroscopic guided biopsy to determine the etiology. Methods: In this study, 252 patients had to undergo trans-vaginal sonography and saline infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
2
14
2
Order By: Relevance
“…24.6% which was close to that observed in Jyotsana et al and Dasgupta et al which was 22.6% and 30.6% respectively but was much lower than observed in Rethu et al study which was 50%. 3,6,4 Atrophic endometrium was present in 10.4% of cases in our study which was close to that observed in Sheetal et al which was 8% and was much less in Reethu et al study i.e. 2%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…24.6% which was close to that observed in Jyotsana et al and Dasgupta et al which was 22.6% and 30.6% respectively but was much lower than observed in Rethu et al study which was 50%. 3,6,4 Atrophic endometrium was present in 10.4% of cases in our study which was close to that observed in Sheetal et al which was 8% and was much less in Reethu et al study i.e. 2%.…”
Section: Discussionsupporting
confidence: 89%
“…8,6 Close to this value, was in the study by Reethu et al and Jyotsna et al who observed normal hysteroscopic findings in 30% and 33.3% of cases, respectively. 4,5 Most common abnormality detected was hyperplastic endometrium i.e.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This finding is reflected in other studies as shown in Table 4. 9,11,12 The least sensitivity for detection with saline infusion sonography was for submucosal fibroids. 5 patients were diagnosed with submucosal fibroids during SIS.…”
Section: Discussionmentioning
confidence: 99%
“…Dasgupta et al [5] evaluated the diagnostic options and accuracy of abnormal uterine bleeding in perimenopausal women found the sensitivity and specificity of TVS for fibroids is 65.7%% and 95.4% respectively.…”
Section: Comparison Of Transabdominal Sonography and Transvaginal Sonmentioning
confidence: 99%